Synthesis of hybrid magnesium hydroxide/magnesium oxide nanorods [Mg(OH)2/MgO] for prompt and efficient adsorption of ciprofloxacin from aqueous solutions. (15th March 2022) - Falyouna, Omar; Bensaida, Khaoula; Maamoun, Ibrahim; Ashik, U.P.M.; Tahara, Atsushi; Tanaka, Kazuya; Aoyagi, Noboru; Sugihara, Yuji; Eljamal, Osama
Abstract: The antibiotic ciprofloxacin (CIP) is recognized as a contaminant of emerging concern because its persistent occurrence in water accelerates the growth of deadly antimicrobial resistance genes (AMRs). For the first time, the conventional precipitation technique was thermally modified to produce hybrid magnesium hydroxide/magnesium oxide nanorods [Mg(OH)2 /MgO] for efficient and rapid adsorption of CIP from water. The successful synthesis of Mg(OH)2 /MgO was confirmed by the outcomes of TEM, EDS, XRD, and FTIR analysis. Mg(OH)2 /MgO exhibited an extraordinary capability to adsorb CIP from water regardless of CIP initial concentration where more than 97% of 200 mg L −1 of CIP was promptly eliminated within 30 min by 0.1 g L −1 of Mg(OH)2 /MgO under neutral pH and room temperature. These results clearly state that Mg(OH)2 /MgO is at least 2-fold efficient and 20-fold faster in removing CIP than the reported nanomaterials with exceptional adsorption capacity higher than 1789 mg g −1 . FTIR analysis for the spent Mg(OH)2 /MgO revealed that bridging complexation with carboxylic group and electrostatic attraction with the positive amine group are the responsible mechanisms for CIP adsorption by Mg(OH)2 /MgO. Moreover, simulated CIP-contaminated river water was efficiently treated by Mg(OH)2 /MgO which proves the promising performance of Mg(OH)2 /MgO in field scale applications. Graphical abstract: Image 1 HIGHLIGHTS: Mg(OH)2 /MgO nanorods were successfully produced by thermal precipitation method. Mg(OH)2 /MgO promptly removed 97% of 200 mg L −1 of CIP within 30 min under neutral pH. Ciprofloxacin adsorption by Mg(OH)2 /MgO was exothermic, spontaneous and physical. Coexisting ions and natural organic matters had no effect on ciprofloxacin adsorption. Bridging complexation and electrostatic attraction are responsible for CIP adsorption.